Knowledge and Attitude of Nepalese Dental Interns towards Adhesives for Removal Dentures - Shrestha, B; Parajuli, PK; Basnet, B B; Adhikari, G.; Pun, DB; Rokaya, D; Bhandari, A (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Denture adhesives play an important role in the retention of removal dentures. This research aimed to study the knowledge and attitude (K&A) of Nepalese dental interns in various Universities/ dental colleges towards adhesives for removal denture (ARDs). Materials and Methods: A survey was conducted among the dental interns of various colleges in Nepal. Pearson’s Chi-square test was carried out to compare the various variables among the Universities/ dental colleges. Rating scale was used for testing the K&A towards denture adhesives. Results: It was found that 86.5% of the dental interns had adequate K&A on ARDs, 87.8% responded that ARD is beneficial for dentures and 95.5% agreed that dentists should regularly inform regarding ARDs to all denture patients. Conclusion: Most of the Nepalese dental interns of various Universities/ dental colleges possessed acceptable K&A on ARDs.